Arthur Schopenhauer - Lewis, Peter, 1947- (Critical lives (London, England), 2012)
Arthur Schopenhauer devoted his adult life to the articulation of a philosophy for the world, a philosophy that would benefit mankind by providing a solution to the riddle of existence. This biography provides a critical introduction to the life and work of the 19th-century German philosopher.